The CaCCHÃ2Π–[formula omitted]2Σ+522and 520Bands Studied by High Resolution Spectroscopy: The Ca–C–C Bending Vibration and Vibronic Interaction - Li, Mingguang; Coxon, John A. (Journal of molecular spectroscopy, 1997)
The CaCCH 522and 520bands in theÃ2Π–X̃2Σ+system, involving the excited Ca–C–C bending vibrations, have been rotationally analyzed via CW dye laser excitation and dispersed fluorescence with a CCD array detector. TheÃ2Πv5= 2 level is subject to Renner–Teller and spin–orbit splittings; in addition,K-resonance interactions are observed between the nearby2Φ and2Π vibronic components. With a full matrix treatment of the six vibronic components (κ2Π, μ2Π, and2Φ) in the upper state, the line positions of the six subbands of the 522band were fitted simultaneously by least squares. The three higher vibronic components, especially the κ2Π1/2component, were found to be perturbed strongly by the lower vibronic components of thev5= 3 level. This perturbation has been analyzed by means of second-order perturbation theory involving theB̃2Σ+electronic state and results in an estimate of the dipolar vibronic interaction parameter, ϵ5(2)ω5= −8.31 cm−1. The 520band was studied through dispersed fluorescence and served to establish an accurate energy of thev5= 2 vibrational level relative to the zero-point vibration level in both theÃandX̃states.